Analysing Linguistic Stylistic Devices in The Adventures of Tom Sawyer and So Long a Letter: A Comparative Appraisal - DADJO, Servais Dieu-Donné Yédia (My University, 2022)
This research work focuses on linguistic stylistic analysis of Mark Twain’s The Adventures of Tom Sawyer and Mariama Bâ’s So Long a Letter. It aims to identify the various translation procedures used in each novel in order to establish a comparison between the different translation procedures and style of each translator of modern and old English. A sampling method has been used to carry out this research work. Thus, one extract has been selected with its corresponding translation from the French and English versions of each novel. The results show that, in The Adventures of Tom Sawyer, the translator has used predominantly adaptation for his translation representing 32.32% in both selected extracts whereas in So Long a Letter, the translator has adopted predominantly literal translation representing a proportion of 28.48% in order to preserve the sustained register of the source text. However, both translators have also used other translation procedures in lower proportions depending on the context orientation. It has been noted that translation methods such as calque has been used only once whereas borrowing is nonexistent in the selected extracts from both literary works.
Keywords: adaptation; borrowing; calque; context; stylistic devices